Integrated Quantum Nanophotonics with Solution‐Processed Materials. Issue 1 (20th November 2021) - Chen, Yueyang; Sharp, David; Saxena, Abhi; Nguyen, Hao; Cossairt, Brandi M.; Majumdar, Arka
Abstract: A key obstacle for all quantum information science and engineering platforms is their lack of scalability. The discovery of emergent quantum phenomena and their applications in active photonic quantum technologies have been dominated by work with single atoms, self‐assembled quantum dots, or single solid‐state defects. Unfortunately, scaling these systems to many quantum nodes remains a significant challenge. Solution‐processed quantum materials are uniquely positioned to address this challenge, but the quantum properties of these materials have remained generally inferior to those of solid‐state emitters or atoms. Additionally, systematic integration of solution‐processed materials with dielectric nanophotonic structures has been rare compared to other solid‐state systems. Recent progress in synthesis processes and nanophotonic engineering, however, has demonstrated promising results, including long coherence times of emitted single photons and deterministic integration of emitters with dielectric nano‐cavities. In this review article, these recent experiments using solution‐processed quantum materials and dielectric nanophotonic structures are discussed. The progress in non‐classical light state generation, exciton‐polaritonics for quantum simulation, and spin‐physics in these materials is discussed and an outlook for this emerging research field is provided. Abstract : Solution‐processed quantum materials provide a route to engineer quantum properties via atomic‐scale synthesis. Moreover, the ability to deterministically position these emitters on any substrate provides a unique opportunity to create a large‐scale quantum photonic circuit. This paper reviews current progress in this field, and outlines the challenges and opportunities for synthesis chemistry, quantum optics, nanophotonics, and quantum information technology.